Evaluation of In-House ELISA for Antirabies Antibodies Detection in Domestic Canine - Yul Fitria; Niko Febrianto; Rahmi E. Putri; Ibenu Rahmadani; Didik T. Subekti (Veterinary Medicine International)
Indonesia is known to be endemic for rabies in several areas, especially in Sumatra, Kalimantan, Sulawesi, and Flores Islands. Currently, vaccinating dogs has been shown to be the most cost-effective strategy for preventing rabies in humans. Postvaccination monitoring should be carried out to evaluate the success of vaccination by measuring antibody titers in serum of vaccinated dogs. Serological methods for monitoring rabies-specific antibody titers can be carried out using enzyme-linked immunosorbent assay (ELISA) methods as recommended by the World Organization for Animal Health (WOAH). Therefore, the development of the in-house ELISA (BukTi-Vet) that we have carried out in order to support postvaccination monitoring in dogs needs to be evaluated for its diagnostic performance compared to commercial ELISA kits. The diagnostic performance of each ELISA kit was evaluated using 111 known positive and 47 negative serums. Each known positive and negative serum will be tested using the three rabies ELISA kits used in this study. BukTi-Vet is an in-house ELISA for the detection of rabies-specific IgG antibodies that have been developed with sensitivity, specificity, and accuracy of 98.19%, 97.87%, and 98.1%, respectively. Based on the value of its positive and negative clinical utility index, BukTi-Vet is excellent for use in immunoassays directed for confirmatory (0.97) as well as screening (0.94) tests. BukTi-Vet shows a very good agreement with both Platelia II and RFFIT, so it is convincing to be further refined into a diagnostic kit. Tests of field sera from dogs vaccinated with various vaccines should be performed to provide more complete information on diagnostic performance. BukTi-Vet showed a very good agreement with RFFIT, while Pusvetma and Platelia II only showed good agreement. The average value of BukTi-Vet compatibility with RFFIT can reach 94%.